Management of intermittent and persistent asthma in adolescent and high school athletes - Del Giacco, S.; Couto, M.; Firinu, D.; Garcia-Larsen, V. (The Journal of Allergy and Clinical Immunology, 2020)
Asthma is the most common chronic condition during childhood and adolescence, affecting an estimated 8% of children and youngsters below 18 years in the United States and the United Kingdom. In adolescent athletes, asthma-like symptoms may represent a common consequence of regular sport practice. Asthma in young athletes poses several challenges, including the ambiguity of definitions and diagnosis of asthma resulting from exercise-induced symptoms, the best pharmacological treatments, and the nonpharmacological options for the management of disease and the challenges inherent to this age group. At a time when the regular practice of sports is increasingly being recommended for a healthy living, the support network around the young athletes is crucial to reduce the impact of asthma on their physical and emotional well-being. In this review, we examine the main issues around the definitions and clinical differentiations of asthma in young sport athletes. We discuss best practice approaches to improve the adherence to the clinical management, including nonpharmacological strategies directed at the family and trainers of athlete adolescents.